2022
DOI: 10.1093/ajcn/nqab366
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and long-term mortality risk after myocardial infarction in the Alpha Omega Cohort

Abstract: Background Population-based studies generally show J-shaped associations between alcohol intake and mortality from cardiovascular diseases (CVD). Little is known about alcohol and long-term mortality risk after myocardial infarction (MI). Objective We examined alcohol intake in relation to all-cause, CVD and ischemic heart disease (IHD) mortality in Dutch post-MI patients of the Alpha Omega Cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, the non-vaccinated cohort might have had poor health associated with alcohol use and smoking which increase mortality in people with severe non-infectious diseases. 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the non-vaccinated cohort might have had poor health associated with alcohol use and smoking which increase mortality in people with severe non-infectious diseases. 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…In men, drinking categories were defined as 0 g/d (abstainers), >0-10 g/d (light), >10-30 g/d (moderate) and >30 g/d (heavy). In women, drinking categories were defined as 0 g/d (abstainers), >0-5 g/d (light), >5-15 g/d (moderate) and >15 g/d (heavy) [23]. In UCC-S-MART, weekly alcohol intake was assessed using a general questionnaire and categorized as 0 drinks / week (none), �1-10 drinks / week (light), 11-20 drinks / week (moderate) and >20 drinks / week (heavy).…”
Section: Baseline Measurementsmentioning
confidence: 99%
“…The data of the Health Professionals Follow-up Study (HPFS) and the Alpha Omega Cohort showed that light to moderate alcohol consumption was inversely related to the all-cause and CVD mortality risks in men by raising HDL-C concentration, reducing inflammation and increasing blood pressure. [11,12] Several prospective cohort studies and meta-analyses have highlighted a reduced risk of CVD outcomes with light to moderate alcohol consumption. [13][14][15] Furthermore, the protective effect of moderate alcohol consumption on the risk of CKD has also been investigated in several cohort studies.…”
Section: Introductionmentioning
confidence: 99%